(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2021)
The aim of this study is to check the redox behavior of Mn (II) and Zn (II) metals before and after interaction with ciprofloxacin in potassium chloride solution by using cyclic voltammetry, chronoamperomety and chronocoulometry methods. Equimolar solutions of Mn (II) and ciprofloxacin were mixed to a ratio of 1:2 and that of Zn (II) and ciprofloxacin to a 1:1 ratio. The results showed that the redox couple involved in Mn (II) as well as Mn(II)-ciprofloxacin interaction systems are quasi-reversible. However, the Zn (II) systems showed reversibility and the Zn(II)-ciprofloxacin interaction was quasi-reversible. The results obtained from the chronoamperometric study showed that after interaction with ciprofloxacin the rate of electrolysis in the metal systems decreased. Bangladesh J. Sci. Ind. Res.56(4), 285-292, 2021